Synthesis of cyclic alkenylsiloxanes by semihydrogenation: A stereospecific route to (Z)-alkenyl polyenes - Elbert, B; Lim, D; Gudmundsson, H; O'Hanlon, J; Anderson, E (Wiley, 2014)
Cyclic alkenylsiloxanes were synthesized by semihydrogenation of alkynylsilanes - a reaction previously plagued by poor stereoselectivity. The silanes, which can be synthesized on multigram scale, undergo Hiyama-Denmark coupling to give (Z)-alkenyl polyene motifs found in bioactive natural products. The ring size of the silane is crucial: five-membered cyclic siloxanes also couple under fluoride-free conditions, whilst their six-membered homologues do not, enabling orthogonality within this structural motif. © 2014 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.